Influence of the type of volatile anesthetic on the development of acute kidney injury after endovascular repair of aortic aneurysm: a randomized controlled trial (DESEVAR study) - Arnalich-Montiel, A.; Barrio-Pérez, I. M.; Burgos-Santamaría, A.; Fernández-Riveira, C.; Lázaro, A.; González-Nicolás, M. A.; Río, J.; Bellón, J. M.; Canal, M. I.; Ligero, J. M.; Quintana-Villamandos, B. (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) frequently occurs after endovascular aortic aneurysm repair (EVAR), leading to significant morbidity and mortality. It is associated with contrast administration, hypovolemia, arterial microembolization due to renal artery manipulation, ischemia–reperfusion syndrome, and other patient comorbidities. However, little is known about the effect of volatile anesthetics on the development of AKI in this context. Therefore, we aimed to investigate renal function in patients anesthetized with desflurane or sevoflurane for EVAR. For this, we conducted a single-center randomized clinical trial involving 80 patients scheduled for elective EVAR under general anesthesia. Patients were randomly assigned to the desflurane or sevoflurane anesthesia group. Biochemical variables of kidney function and biomarkers for AKI were studied at three different time points: before surgery, after surgery, and 24 h after surgery. Plasma creatinine, cystatin C, estimated glomerular filtration, uric acid, and kidney injury molecule-1 did not significantly change between both groups. A mixed linear model demonstrated a significant interaction (p = 0.01) of plasma neutrophil gelatinase-associated lipocalin (NGAL) between sevoflurane and desflurane. Both groups showed a progressive increase in plasma NGAL (sevoflurane 3.713 ng/mL, p < 0.001 and desflurane 1.774 ng/mL, p < 0.001) when comparing the moment before surgery with respect to 24 h after surgery. However, sevoflurane caused a higher plasma NGAL concentration than desflurane after 24 h of surgery (8.66 ± 5.09 ng/mL vs. 6.51 ± 3.86 ng/mL, P = 0.03). Desflurane was associated with a lower postoperative AKI than sevoflurane in patients undergoing EVAR. Further research is required to corroborate our results and evaluate the clinical importance. Trial registration: EudraCT: 2016-003906-16; ClinicalTrials.gov: NCT03917186.